Preface - Tiina RANDMA-LIIV; Vitalis NAKROŠIS; György HAJNAL (Transylvanian Review of Administrative Sciences, 2011)
The contributions in this special issue reflect upon the results of the European Union’s COST Action IS0601 (2007-2011) called CRIPO (Comparative Research into Current Trends in Public Sector Organization), which was led by the prominent public administration scholars Geert Bouckaert, Per Lægreid and Koen Verhoest. The main objective of the CRIPO project was to increase knowledge about current trends in public sector organization in Europe in order to contribute to theoretical knowledge and optimize methodologies, and thus to inspire sound and policy-relevant research conclusions. The CRIPO project brought together scholars on a European platform for comparative and longitudinal research, which led to empirical, theoretical and methodological advancements in the field. Ultimately 23 European countries and 95 individual researchers cooperated in a research network organized around several topics, such as population and proliferation of public sector organizations, autonomy, steering and control, performance, accountability and coordination of public sector agencies. From Central and Eastern Europe (CEE), Croatia, Estonia, Hungary, Lithuania, Romania and Slovakia participated actively in the project.